Synbiotic Smallanthus Sonchifolius (Yacon) and Streptococcus Salivarius Inhibit Candida Albicans biofilm formation - Rismayuddin, Nurul Alia Risma; Syed Nasarudin, Syarifah Nurhikmah Izzati; Ibrahim, Nurul Ruziantee; Alnuaimi, Ali; Arzmi, Mohd Hafiz (AIP Publishing, 2023)
Oral biofilms are comprised of extracellular polysaccharides and polymicrobial microorganisms. The objective of this study was to determine the effect of synbiotic Smallanthus sonchifolius (yacon) with Streptococcus salivarius K12 (K12) on polymicrobial biofilm formation of Candida albicans with the hypothesis that polymicrobial biofilm biomass of C. albicans is inhibited by synbiotic S. sonchifolius with K12. Initially, disk diffusion and well diffusion assay were conducted to determine the susceptibility of C. albicans towards S. sonchifolius and K12. Following that, C. albicans was mixed with S. salivarius in nutrient broth (NB) or RPMI-1640 to determine the effect of probiotic on the polymicrobial biofilm. To determine the effect of synbiotic, similar protocol was repeated by adding 800 mg mL-1 of S. sonchifolius aqueous extract extract into the same followed by a 72 h incubation. Finally, biofilm biomass was measured using a crystal violet assay. C. albicans ATCC MYA-4901, ALC2 and ALC3 were found to be susceptible to S. sonchifolius extract and S. salivarius K12. However, the biofilm of all of C. albicans strains ATCC MYA-4901, ALC2 and ALC3 were found to reduce ranged in between 20% to 39.4% when co-cultured with synbiotic compared to prebiotic culture in NB. In conclusion, synbiotic S. sonchifolius with K12 inhibit polymicrobial biofilm. This indicates the potential use of synbiotic in dental application for the prevention C. albicans infection.